Posttraumatic coccydynia in a 7-year-old girl treated with coccygectomy - Ayman Alkhamisy; Mohamad Morjan; Walaa Abbas (Elsevier, 2021)
Coccydynia is very rare in children and is most often caused by a traumatic event. A 7-year-old girl presented to an outpatient clinic with a long history of post-traumatic coccydynia for the past eight months, not responding to conservative management with NSAIDs and associated with the inability of sitting. On examination, a rigid tender bony protuberance in the coccygeal area was palpated. No inflammatory signs were noticed. All lab investigations were normal. MRI of the lumbosacral spine revealed straightening of the coccyx without evidence of posterior luxation. Because of the intractable pain that did not respond to conservative management that interferes with the sitting position, the girl underwent coccygectomy through a midline posterior sagittal incision followed by a favorable clinical outcome. Conclusion: The principles of treating coccydynia in children are similar to those of adolescents and adults, with due regard to the rare congenital anomalies that may hide behind.